Learning, Marginalization, and Improving the Quality of Education in Low-income Countries - Wagner, Daniel A.; Castillo, Nathan; Grant Lewis, Suzanne (Open Book Publishers, 2022)
Improving learning evidence and outcomes for those most in need in developing countries is at the heart of the United Nations' Sustainable Development Goal on Education (SDG4). This timely volume brings together contributions on current empirical research and analysis of emerging trends that focus on improving the quality of education through better policy and practice, particularly for those who need improved 'learning at the bottom of the pyramid' (LBOP). This volume brings together academic research experts, government officials and field-based practitioners. National and global experts present multiple broad thematic papers - ranging from the effects of migration and improving teaching to the potential of educational technologies, and better metrics for understanding and financing education. In addition, local experts, practitioners and policymakers describe their own work on LBOP issues being undertaken in Kenya, India, Mexico and Ivory Coast. The contributors argue persuasively that learning equity is a moral imperative, but also one that will have educational, economic and social impacts. They further outline how achieving SDG4 will take renewed and persistent effort by stakeholders to use better measurement tools to promote learning achievement among poor and marginalized children. This volume builds on the second international conference on Learning at the Bottom of the Pyramid (LBOP2).* It will be an indispensable resource for policymakers, researchers and government thinktanks, and local experts, as well as any readers interested in the implementation of learning equity across the globe.